PENANAMAN NILAI PENDIDIKAN KARAKTER PADA SISWA DI SEKOLAH MENENGAH PERTAMA ASY-SYARIFIYAH PURWASARI KARAWANG - Yoga Muhammad Vicri Riyanto (Universitas Islam Madura, 2023)
Character education is a priority program for the Asy-Syarifiyah Middle School Institute in Purwasari Karawang because character is the goal of implementing education itself, character education has its own charm for researchers, so the research aims to find out how far the implementation of character education values ​​is instilled in students at Asy- Syarifiyah Purwasari Karawang. The research method used was a descriptive qualitative approach and the subjects of this study were students of SMP-Asyarifiyah Purwasari Karawang. While documentation and observation techniques as well as interviews are used as research tools. The research findings related to character education are character education on a very important basis to be applied to students which can then influence students' attitudes in participating in classroom learning. Because school is a place where students find themselves and form moral and noble character. Aspects of character education in question are discipline, courtesy compensation, leadership spirit, and so forth. So the implication of this research is that education practitioners can easily predict the implementation of character education in the future, both in terms of its success or those that are included in the unsuccessful category and become a follow-up program in order to gain wider success.